PENGARUH KARAKTERISTIK AUDIT TERHADAP PENGHINDARAN PAJAK - Vivi Tandean; Martha Carolina (Jurnal Budget : Isu dan Masalah Keuangan Negara, 2022)
Tax avoidance is carried out by taxpayers so that the company's goals are still achieved by obtaining maximum profits. This study aims to determine the effect of audit cost on tax avoidance, the effect of auditor specialization on tax avoidance, and the effect of auditor tenure on tax avoidance. The results of the study conclude that the audit cost (X1) has a significant positive impact on the tax avoidance variable (Y), the Auditor Specialization variable (X2) has no effect on the tax avoidance variable (Y), the auditor tenure variable (X3) has no effect on the avoidance variable (Y).